BIMBINGAN DAN PENYULUHAN TENTANG TEKNIK PEMBUATAN HOUSE JOURNAL DAN PR WRITING UNTUK PEMBERDAYAAN IBU-IBU RW 21 KELURAHAN PURWANTORO KOTA MALANG - Fullchis Nurtjahjani (Publisher UPT P2M Politeknik Negeri Malang, 2017)
Activity management at each institution or organization concerned with developing the potential and lead a team or group of people in a single unit, in utilizing existing resources to achieve specific goals within the organization that has been designated. Writing is not merely a regular job / skills umun but a combination of brain work that is supported with a special ability to combine an idea. Therefore, to be a good communicator necessary knowledge and language skills were good, insightful with full of creativity to manage news, press releases, articles or features are arranged in dense and short but interesting for the readers or the target audiencenya., So it is necessary a guidance and training, especially for mothers PKK RW 21 Sub Purwantoro Malang on techniques, motivation and skill of making House Journal and PR Writing in theorganization.